Nonlinear Instability of Equilibrium Solution for the Ginzburg-Landau Equation (Journal of Partial Differential Equations, 2005)
We study the nonlinear instability of plane wave solutions to a Ginzburg- Landau equation with derivatives. We show that, under some condition in coefficient of the equation, these waves are unstable.